Transgender and Gender-nonbinary Patient Satisfaction after Transmasculine Chest Surgery. Issue 3 (March 2021) - Bustos, Valeria P.; Bustos, Samyd S.; Mascaro, Andres; Del Corral, Gabriel; Forte, Antonio J.; Ciudad, Pedro; Kim, Esther A.; Langstein, Howard N.; Manrique, Oscar J.
Abstract : Background: Transmasculine chest surgery is the most common surgery performed in transmasculine patients, with high overall acceptance and low postoperative complication rates. Trends have shown clear improvement in quality of life and satisfaction. However, to the best of our knowledge, overall patient satisfaction after transmasculine chest surgery and associated factors are largely unknown. The aim of this study is to estimate the overall patient satisfaction in transgender men and nonbinary population after transmasculine chest surgery and to assess associated factors. Methods: A systematic review was conducted by searching literature in several databases. Meta-analyses of prevalence with a random-effect model for overall and subgroup prevalence were performed. Meta-regression, publication bias, and sensitivity analyses were conducted. Results: A total of 1052 transmasculine patients underwent any type of transmasculine chest surgery. The pooled overall postoperative satisfaction was 92% [95% confidence interval (CI) 88–96%]. In the subgroup metanalysis, patient satisfaction after periareolar mastectomy was 93% (CI 88%–97%) and after mastectomy with or without free nipple grafting was 90% (CI 84%–95%). Patient satisfaction for studies with mean follow-up >1 year was 91% (CI 83%–97%) and for mean follow-up of 1 year or less was 93% (CI 89%–96%). Conclusions: This study shows a high level of satisfaction in transmasculine chest surgery for both techniques, which remain stable over time. Also, our results show that this procedure impacts patient satisfaction beyond chest appearance and surgical outcomes. This corroborates its broad acceptance and the improvements in the standard of care, and decision-making approach. Abstract : Supplemental Digital Content is available in the text.